Korupsi dan Gaya Satire pada YouTube Meet Nite Live - Wikan Arum Pakerti; Dyva Claretta (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study explores how corruption discourse is constructed in the Meet Nite Live talk show broadcasted on Metro TV’s YouTube channel, using Rodney H. Jones’ Digital Discourse Analysis approach. One episode was analyzed through four key elements: text, context, action and interaction, as well as ideology and power. The findings reveal that satire, through irony, humor, and parody, serves as a strategic method to deliver sharp yet engaging political criticism. In the context of digital media, audiences actively respond via comments—expressing support, frustration, or critical reflection. The show also constructs a narrative that normalizes corruption as a systemic issue, while still inviting public awareness through creative and participatory communication strategies.